Leadership Skills and their Impact on Strategic Planning: Applied Research in the Iraqi Ministry of Planning - القيسي فاضل حمد; محمود زيد خوام (Journal of Economics and Administrative Sciences, 2015)
The present search addressed the " leadership skills and their impact on strategic planning " Where has the objective of leadership skills and strategic planning of increasing importance at the present time , for being fairly modern topics ,which have a tremendous impact on the success of organizations.. Objective of the research to find out what leadership skills available in the Iraqi Ministry of Planning and the most important of the ministry, and knowledge of the relationship and influence between leadership skills and strategic planning , the use of system the (SPSS) Statistical to get to the results, was chosen the Ministry of Planning of field research , both in the ( headquarters Ministry and the Central Bureau of Statistics and the Centre for Management Development ) and was search Community from ( Deputy Minister , General Manager , Deputy General Manager, head of Department ) and the number (89) , but the number of questionnaires returned was (73) questionnaire , formulated the hypothesis link the main contact between leadership skills and planning strategic ramifications of which four hypotheses subsidiary, as formulated three hypotheses influence between leadership skills and strategic planning The ramifications of each of the four sub-hypotheses , the research found that all hypotheses link and influence between the variables and sub is a powerful and significant moral, as recommended by search a number of recommendations most important: to emphasize the importance of leadership skills in the ministry because of its significant impact on strategic planning, a lack of focus on the skill without the other , but the use of all leadership skills at all administrative levels , and the intensification of seminars , conferences and training sessions on the themes of leadership skills and strategic planning , and the emphasis on work teams in order to exchange experiences and skills